1993
DOI: 10.1254/jjp.62.35
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Induced Increase in Oxidative Metabolism of Dissociated Mammalian Brain Neurons: Effect of Extract of Ginkgo Biloba Leaves

Abstract: ABSTRACT-Acetylcholine (ACh) release from the motor nerve terminal in the streptozocin-induced diabetic state was studied in mouse phrenic nerve-diaphragm muscle preparations. Electrically evoked re lease of 3H-ACh from the preparation preloaded with 3H-choline was measured during two consecutive periods of stimulation (S1 and S2). In diabetic mice, the amount of 3H-ACh release during S2 was decreased, and the evoked ACh release declined more steeply with successive stimulation periods than in normal ddY mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…These later observations could help explain the reduction in QC seen in our diabetic mice. In accord with our study, Kimura et al (24) found a reduction in stimulus-evoked transmitter release from motor nerve endings of diabetic mice. Furthermore, the sternomastoid muscle of nonobese diabetic mice exhibits an altered distribution of muscle end plate AChRs with the formation of abnormal receptor islands and motor nerve terminal sprouts (28) similar to those we report for the STZ model of diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…These later observations could help explain the reduction in QC seen in our diabetic mice. In accord with our study, Kimura et al (24) found a reduction in stimulus-evoked transmitter release from motor nerve endings of diabetic mice. Furthermore, the sternomastoid muscle of nonobese diabetic mice exhibits an altered distribution of muscle end plate AChRs with the formation of abnormal receptor islands and motor nerve terminal sprouts (28) similar to those we report for the STZ model of diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…11 Evidence for possible transmission failure as a result of reduced synaptic safety factor in diabetes comes from studies showing reduced acetylcholine release in streptozotocin (STZ)-based murine models of diabetes. 22,23 At the same time, however, increased acetylcholine sensitivity has also been shown in STZ-induced diabetes. 24,25 Together with the observation that muscles from both STZ mice and db/db mice show decreased acetylcholinesterase gene expression, 25 this could indicate that the potential impairment of neuromuscular transmission arising from reduced acetylcholine release is compensated, at least to some extent, by mechanisms that increase the postsynaptic effect of the acetylcholine that is actually released.…”
Section: Role Of Neuromuscular Transmission Failure In Forcementioning
confidence: 96%
“…8 Accordingly, the electrically evoked release of ACh from the phrenic nerve is reduced. 13 Thus, alterations in the structure and function of the ␣-motoneurons may contribute to the decrements in muscle strength in diabetics beyond the losses resulting from reductions in muscle size. It is also possible that changes in the postsynaptic membrane at the NMJ contribute to reduced muscle function in diabetics.…”
mentioning
confidence: 99%